2016
DOI: 10.3389/fphys.2016.00259
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide Modulates Connexin Function through a Lipid Peroxidation-Dependent Process: A Hypothesis

Abstract: Hemichannels are ion channels composed of six connexins (Cxs), and they have the peculiarity to be permeable not only to ions, but also to molecules such as ATP and glutamate. Under physiological conditions they present a low open probability, which is sufficient to enable them to participate in several physiological functions. However, massive and/or prolonged hemichannel opening induces or accelerates cell death. Therefore, the study of the molecular mechanisms that control hemichannel activity appears to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 79 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…This damage can be caused by mtROS produced or directly by CO, as previously reported [10]. Mitochondrial ROS [16] and lipid peroxidation [41] are two conditions suggestive of ferroptosis, a type of cell death independent of caspase activation but triggered by oxidative stress, often catalyzed by iron or promoted by reduced antioxidant defenses or immune signaling from tumor microenvironment [42]. Because we detected either oxidative stress and lipoperoxidation in cells treated with CORM and chemotherapeutic drugs, we cannot exclude that CORM acted by inducing ferroptotic death.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This damage can be caused by mtROS produced or directly by CO, as previously reported [10]. Mitochondrial ROS [16] and lipid peroxidation [41] are two conditions suggestive of ferroptosis, a type of cell death independent of caspase activation but triggered by oxidative stress, often catalyzed by iron or promoted by reduced antioxidant defenses or immune signaling from tumor microenvironment [42]. Because we detected either oxidative stress and lipoperoxidation in cells treated with CORM and chemotherapeutic drugs, we cannot exclude that CORM acted by inducing ferroptotic death.…”
Section: Discussionmentioning
confidence: 59%
“…This effect may be attributed to the direct inhibition of mitochondrial complex IV by CO [16] and/or increased accumulation of chemotherapeutic drugs within cells, caused by reduced mtATP production. Alternatively, as already observed for NO and H 2 S [5][6][7], CO may also directly reduce the activity of ABC transporters: it has been reported that CO oxidizes the cysteines of integral membrane proteins, triggering a radical cascade at the membrane protein-lipid interface that alters protein functions [41]. Our CO-donor also induced a reduction in the catalytic efficacy of ABCB1, ABCC1 and ABCC5 in cell lines with the highest levels of these transporters, suggesting a lower efficiency in efflux of the respective chemotherapeutic substrates.…”
Section: Discussionmentioning
confidence: 75%
“…Our group and others have proposed that molecules associated to oxidative stress modulate hemichannel opening [70,[83][84][85][86]. For example, Cx43 hemichannel S-nitrosylation exacerbates hemichannel activity in cerebral ischemia [87] and inflammatory models [62].…”
Section: Hemichannelsmentioning
confidence: 99%
“…We also found that CORM-2 induces carbonylation of purified Cx46 ( Leon-Paravic et al, 2014 ), but the amino acids modified have not been identified. Based on these observations, we have proposed that CO carbonylates extracellular Cx46 cysteines through lipid peroxides, which reduces Cx46 hemichannel activity, with a protective effect against oxidative stress and cataract development ( Retamal, 2016 ).…”
Section: Cx46 Posttranslational Modifications and Their Potential Rel...mentioning
confidence: 99%